(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2016)
Kelantan State recorded the highest in terms of acreage for tobacco plantation with consists of 77.94 %. Tobacco plantation was known to be the most risky job among Kelantanese due to extensive usage of pesticide and fertilizer. This study was conducted to identify the differences between male and female in Best Management Practices (BMPs) for tobacco cultivators in Bachok as well as to relate it with the fertilizers and pesticides related diseases in Bachok District, Kelantan, Malaysia. The results revealed that, the correlation between wearing proper PPEs and gender (p<0.05) and between chronic diseases and gender (p<0.05) were significant. Female cultivators they are more concern about their health compared to the male. Meanwhile, 49% of male and 25 % of female cultivators claimed that they had the acute illnesses. On the other hand, the health data in 2010 obtained from the Bachok District Health Center showed that, acute upper respiratory tract infections (19,641 cases) and other disease of the respiratory system (16,484 cases) recorded the highest cases followed by dermatitis (5,300 cases), conjunctivitis (2,582 cases), urticarial (1,689 cases), impetigo (1,387 cases), poisonings (548 cases), asthma (450 cases) and bronchitis (8 cases). It could be concluded that, the female planter are more health conscious and it is revealed in this findings where they wore PPEs at all times when dealing with chemicals.